Prevalence of fibromyalgia among university students and its impact on their health-related quality of life: a survey-based study from Egypt - Samar Tharwat; Nourhan Ramadan Mosad; Kerolos Ebrahim Abdelmessih; Eman Moatamed; Mohamed Rihan; Nouran Osama; Norhan Sallam; Yara Elsayed (BMC, 2023)
Abstract Background University students are more likely to experience stress, anxiety, and depression. All these factors are regarded as psychological contributors to fibromyalgia syndrome (FMS). Aim To investigate the prevalence and determinants of FMS among university students and its impact on their health-related quality of life (HRQoL). Methods This online survey-based study involved 2146 university students who were recruited from various faculties at several Egyptian universities. The participants' demographics, medical history, academic pursuits, and sleep data were collected. To identify the existence of FMS, the 2016 updates to the 2010/2011 FMS diagnostic criteria were used. Additionally, the participants completed the Short-Form Health Survey-36 (SF-36). Results The mean age was 21.26 ± 2.015 years and 76% were females. Of 2146 students, 266 (12.4%) fulfilled the criteria of FMS. FMS group had a significantly lower age (p < 0.001) with predominant female gender (89.5% vs. 74.1%, p < 0.001), positive family history of FMS (8.6% vs. 3.7%, p < 0.001), previous history of traffic accident (10.2% vs. 6.8%, p = 0.045), lower level of physical activity (p = 0.002),higher time spent in study per week (p = 0.002), lower sleep time (p = 0.002), with frequent walk up (p < 0.001) and snoring (p < 0.001) during sleep. Regarding HRQoL, students with FMS had significantly lower scores than students without in all domains. Conclusion FMS is prevalent among Egyptian university students and is linked to female gender, positive family history, lower levels of physical activity, and more time spent studying each week. FMS has a negative impact on HRQoL. Therefore, early detection and treatment are recommended.